A systematic Mendelian randomized study of the effects of the gut microbiome and immune cells on pancreatic neuroendocrine tumors - Fangsheng Chen; Yuan Zhou; Xinwen Mao; Ronggui Lin; Heguang Huang (Discover Oncology)
Abstract Pancreatic neuroendocrine tumors (pNETs) are a rare subset of pancreatic cancers often diagnosed late and characterized by complex behaviors. Recent evidence suggests the gut microbiome (GM) significantly influences various diseases by modulating the immune system. This study utilized a Mendelian randomization (MR) approach to investigate the causal relationship between GM and pNETs, using single nucleotide polymorphism data as instrumental variables. Two-sample MR analysis identified significant correlations between GM and immune cell types. The study found eight specific GMs affecting pNETs risk: the family Sutterellaceae (OR: 1.52, 95% CI 1.10–2.10, p = 0.01), the genus Paraprevotella (OR: 1.34, 95% CI 1.05–1.72, p = 0.02), the species Paraprevotella unclassified (OR: 1.40, 95% CI 1.08–1.81, p = 0.01), and the species Ruminococcus torques (OR: 1.45, 95% CI 1.12–1.89, p = 0.01) increased risk, while the class Gammaproteobacteria (OR: 0.75, 95% CI 0.57–0.98, p = 0.04), the family Acidaminococcaceae (OR: 0.70, 95% CI 0.52–0.94, p = 0.02), the species Paraprevotella xylaniphila (OR: 0.72, 95% CI 0.54–0.96, p = 0.03), and the species Bacteroides finegoldii (OR: 0.68, 95% CI 0.51–0.91, p = 0.01) decreased it. Mediation analysis indicated the species Ruminococcus torques mediated the effect of CD25 on CD45RA+ CD4 non-regulatory T cells on pNETs, accounting for 3.6% of the total effect. This study provides evidence suggestive of a potential causal role of specific GM compositions in pNETs progression and their mediation through immune cell signatures. However, mechanistic studies are required to further validate this relationship. Graphical abstract